2014
DOI: 10.1371/journal.pone.0104847
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Organic Solvents on Catalytic Behaviors and Cell Morphology of Whole-Cell Biocatalysts for Synthesis of 5′-Arabinocytosine Laurate

Abstract: A whole-cell based method was developed for the regioselective synthesis of arabinocytosine laurate. Among the seven kinds of bacteria strains tested in the acylation reaction, Pseudomonas fluorescens gave the highest productivity and a higher 5′-regioselectivity than 99%. Compared with pure organic solvents, the use of organic solvent mixtures greatly promoted the yield of the whole-cell catalyzed reaction, but showed little influence on the 5′-regioselectivity. Of all the tested solvent mixtures, the best re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The precipitation of protein and other insoluble matters by RapidRAW reagent is a result of organic The reagent is designed based on previous studies about solvents effect on enzyme and cell structure where dehydration caused by solvents was reported as the main process contributing to cell disruption [18,19]. However, the reagent capacity is currently unable to differentiate 100% pure honey with low percentage of adulterated honey or contaminated pure honey.…”
Section: Discussionmentioning
confidence: 99%
“…The precipitation of protein and other insoluble matters by RapidRAW reagent is a result of organic The reagent is designed based on previous studies about solvents effect on enzyme and cell structure where dehydration caused by solvents was reported as the main process contributing to cell disruption [18,19]. However, the reagent capacity is currently unable to differentiate 100% pure honey with low percentage of adulterated honey or contaminated pure honey.…”
Section: Discussionmentioning
confidence: 99%
“…The resultant adapted culture contained xylanase activity of 25 U mL À1 . The nonadapted culture (not exposed to any ILs) also harvested at its log phase contained xylanase activity of 55 U mL C with addition of non-adapted cell extract for 48 h at 40 C.…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43] Solvents are reported to damage the integrity of cellular membranes thereby causing changes in permeability. 40,44 The extreme shrinkage and shrivelled appearance of the cellular structure may possibly be due to the leakage of the intracellular components. The SEM images showed that the IL [BMIM] [BF 4 ] is toxic and damaging to S. thermophile cells.…”
Section: Viability Studies By Mtt Assay In the Presence Of Compatiblementioning
confidence: 99%
“…2b) and found both free and immobilized Ulp1 work well when ethanol was up to 20% (v/v). Stability in these solvents indicates that DMSO or ethanol can be added to minimize bacterial growth and be useful for some catalyzing and modification reactions (Yang et al 2014). Interestingly, SUMO was degraded when no DMSO was added while no perspective degradation existed after 10% DMSO was added ( Supplementary Fig.…”
Section: Effects Of Chemical Reagents Addition On Enzyme Activitymentioning
confidence: 99%